2013
DOI: 10.1073/pnas.1222787110
|View full text |Cite
|
Sign up to set email alerts
|

Strain history dependence of the nonlinear stress response of fibrin and collagen networks

Abstract: We show that the nonlinear mechanical response of networks formed from un-cross-linked fibrin or collagen type I continually changes in response to repeated large-strain loading. We demonstrate that this dynamic evolution of the mechanical response arises from a shift of a characteristic nonlinear stress-strain relationship to higher strains. Therefore, the imposed loading does not weaken the underlying matrices but instead delays the occurrence of the strain stiffening. Using confocal microscopy, we present d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
203
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(227 citation statements)
references
References 42 publications
23
203
0
1
Order By: Relevance
“…We must point out that local fiber recruitment is closely related to the inelastic (history-dependent) bulk response of biopolymer networks (27)(28)(29). In particular, mechanical straining accelerates the dissociation of weak cross-links (30), leading to macroscale plastic deformation of the matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We must point out that local fiber recruitment is closely related to the inelastic (history-dependent) bulk response of biopolymer networks (27)(28)(29). In particular, mechanical straining accelerates the dissociation of weak cross-links (30), leading to macroscale plastic deformation of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mechanical straining accelerates the dissociation of weak cross-links (30), leading to macroscale plastic deformation of the matrix. It had been shown that such an effect is more prominent at long timescales (27) and large strains (28,29), whereas it diminishes with the addition of permanent covalent cross-links (28,29). In contrast, networks that only have weak crosslinks are more dissipative and undergo larger stress relaxations (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, collagen type I exhibits a viscoelastic behavior, they store elastic energy and partially relax internal stress through dissipative process [33]. The fiber crosslinkers exhibit a complex behavior and when they are subjected to a high level of force they can break down.…”
Section: Discussionmentioning
confidence: 99%
“…9 Thus, it is important to consider the effects of both the vast range and progressive increase in stress experienced by fully formed clots. Marked changes in the structure and rheological properties of the clot can arise as a consequence of shear stress through several different mechanisms including strain-stiffening of the fibrin network, 11 strain-stiffening of individual fibrin fibres, 12,13 protein unfolding of stretched fibres, 14 unfolding of fibrin monomers, 15 yielding of branching points, 16 slippage of protofibrils within fibres, 17 and breakage of individual fibrin fibres. 18,19 The propensity of the formed blood clot to macroscopically fracture may be influenced by all of the aforementioned mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Large Amplitude Oscillatory Shear (LAOS) has been used in a controlled strain manner to perform repeated large strain loadings on fibrin clots and the data were presented using Lissajous-Bowditch curves. 17,25 Using repeated cyclic strain loadings, Münster et al 17 showed the ability of un-crosslinked fibrin clots to adapt to stress through the slippage of protofibrils. Moreover, the LAOS studies of van Kempen et al 25 revealed several nonlinear features of fibrin clots, including time-dependent softening, intra-cycle strain stiffening, and increased viscous dissipation with increased strain, illustrating the usefulness of LAOS in capturing rich nonlinear behaviour.…”
Section: Introductionmentioning
confidence: 99%